Numerical study of a hybrid photovoltaic thermal desalination system - Noble, Cole Douglas (Energy Research Centre, 2017)
The world as we know it depends highly on fossil fuels. However, these resources are finite, and evidence suggests that their combustion contributes to climate change. In addition, fresh water supplies are becoming scarcer amidst instabilities in weather patterns and unsustainable water consumption levels. As such, photovoltaic (PV) systems have emerged as a potential off-grid alternative to traditional fossil fuel energy generation. However, their widespread proliferation is, in part, inhibited by their inefficiency as less than 20% of incident solar energy is converted to electrical energy. Hybrid photovoltaic thermal (PV/T) desalination systems have emerged as one way of improving the overall efficiency of PV panels as they make use of the waste heat from panels to aid the desalination process in solar stills. Solar stills have been modelled with software for the purpose of performance optimisation, but most of them do not account for the still's view factor in the calculation of internal radiative heat transfer coefficient. The aim of this study was to construct a numerical model for a hybrid PV/T desalination system and determine its accuracy. The modelling was undertaken in Matlab and was validated against experimental data from a previous study using Root Mean Square Error (RMSE) and correlation values. It was observed that the model performed adequately as a water yield RMSE value of 22.0% was found. Furthermore, it was found that the view factor reduces the RMSE of hourly water yield from 28.9% to 22.0% and improves the correlation factor from 0.9890 to 0.9896. Sensitivity analyses were performed with annual data from Stellenbosch, South Africa (33.935°S 18.7817°W) and indicated an optimal water depth of 0.02m for high water yield, and 0.04m for high electrical energy yield. Also, an optimal panel tilt angle of 30° was found for both water and electrical energy yields and optimal cover tilt angles of 40° and 60° were observed for maximum water and electrical yields respectively. The conclusion of this study was that the incorporation of a view factors does indeed improve the accuracy of hybrid PV/T desalination system models. Additionally, low basin water depth is favourable for high water yields and high basin water depth, for high electrical energy yields. Furthermore, a panel tilt angle of 30° is optimum for both types of yield. Finally, the still cover tilt angle should be set to 40° for optimal water yields, but should be as steep as possible for optimal electrical energy yields.